ATPase-dependent role of the atypical kinase Rio2 on the evolving pre-40S subunit - Ferreira-Cerca, Sébastien (2012)
Ribosome synthesis involves dynamic association of ribosome biogenesis factors with evolving pre-ribosomal particles. Rio2 is an atypical protein kinase required for pre-40S subunit maturation. We report the crystal structure of eukaryotic Rio2 with bound ATP/Mg(2+). Unexpectedly, the structure reveals a phosphoaspartate intermediate with ADP/Mg(2+) in the active site, typically found in Na(+)-, K(+)- and Ca(2+)-ATPases. Consistent with this finding, ctRio2 exhibits a robust ATPase activity in vitro. In vivo, Rio2 docks on the ribosome with its active site occluded, and its flexible loop positioned to interact with the pre-40S subunit. Moreover, Rio2 catalytic activity is required for its dissociation from the ribosome, a necessary step in pre-40S maturation. We propose that phosphoryl transfer from ATP to Asp257 in Rio2’s active site and subsequent hydrolysis of the aspartylphosphate could be a trigger to power late cytoplasmic 40S subunit biogenesis.